Canine Distemper Virus in Asiatic Lions of Gujarat State, India - Mourya, Devendra T. (Emerg Infect Dis, 2019)
In September 2018, an epizootic infection caused by canine distemper virus emerged in an Asiatic lion population in India. We detected the virus in samples from 68 lions and 6 leopards by reverse transcription PCR. Whole-genome sequencing analysis demonstrated the virus strain is similar to the proposed India-1/Asia-5 strain.